2018
DOI: 10.1021/acs.jpcb.7b10469
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Diffusion in Various Carbonated Beverages: A Molecular Dynamics Study

Abstract: Carbonated beverages are widely enjoyed in spare time, yet there remain many physical and chemical processes clouded at the molecular level. In this report, we employ molecular dynamics simulations to estimate the diffusion coefficients of CO and the molecular origin of its variations in three model systems with characteristic features of champagnes, sugar-based cola drinks, and club sodas. The computed diffusion coefficients of CO are in good agreement with experimental data. Analyses of hydrogen bonding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
2
18
0
Order By: Relevance
“…From this definition of H bonds, they found that EtOH created roughly fifty times more H bonds than CO 2 when water molecules were described by the SPC/E and TIP5P models. This result, later confirmed by Lv et al [54], contributed to account for the smallness of EtOH diffusion coefficients compared with CO 2 ones. Although it is hard to predict how an accurate description of the rotation of EtOH methyl groups would precisely alter the number of H bonds involving EtOH molecules, we may expect an increase of this number.…”
Section: Possible Improvements Of the Theoretical Approachsupporting
confidence: 62%
“…From this definition of H bonds, they found that EtOH created roughly fifty times more H bonds than CO 2 when water molecules were described by the SPC/E and TIP5P models. This result, later confirmed by Lv et al [54], contributed to account for the smallness of EtOH diffusion coefficients compared with CO 2 ones. Although it is hard to predict how an accurate description of the rotation of EtOH methyl groups would precisely alter the number of H bonds involving EtOH molecules, we may expect an increase of this number.…”
Section: Possible Improvements Of the Theoretical Approachsupporting
confidence: 62%
“…The agreement with 13 C NMR data of CO 2 diffusion coefficients derived from MD simulations using the OPC and TIP4P/2005 water models demonstrate that a low enthalpy, high number of H bonds, and low value of TOPs are the required conditions to hope for any proper modeling of CO 2 diffusion in carbonated hydroalcoholic solutions. Moreover, a number of past studies, including some of ours, considered the TIP5P water model as a candidate to investigate molecular diffusion in carbonated beverages, 7,10,15 a habit that should be discarded according to these results.…”
Section: Resultsmentioning
confidence: 99%
“… 14 By assuming champagnes as homogeneous and isotropic liquids on average, they were able to get CO 2 diffusion coefficients over the whole experimental temperature range, namely, from 277 to 293 K. Values obtained at temperatures above 285 K with the SPC/E water model were in close agreement with NMR measurements performed on carbonated hydroalcoholic solutions and brut-labeled champagnes. 7 However, the agreement was much more questionable at low temperatures ( T < 285 K) where theoretical CO 2 diffusion coefficients strongly underestimated the experimental value at T = 277 K and overestimated it at T = 281 K. Moreover, CO 2 diffusion coefficients obtained with the TIP5P water model overestimated experimental data over the whole temperature range, a result later confirmed by alike studies conducted by Lv et al., 15 although the temperature dependence seemed qualitatively correct. Finally, convergence issues due to the relatively short duration of the production runs (i.e., 1 ns) motivated the authors to employ replica exchange dynamics, a parallel approach that might not be needed to get accurate values of CO 2 diffusion coefficients in a hydroalcoholic solution.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…31,32 Determining CO 2 diffusion at the various temperature and pressure conditions and in different solvents like pure water, brine, n-alkanes, and beverages, and in the presence of other gases is an ongoing interest in the recent studies. [33][34][35][36][37][38][39][40] To follow up the previous studies and pave the way for future studies regarding impure CO 2 sequestration, in this paper we investigate the effect of impurity on the diffusion coefficient of CO 2 during coinjection of CO 2 with N 2 and SO 2 . Two levels of impurity are considered for two types of impurities and simulation conditions are chosen in a way to cover a wide range of the operational conditions.…”
Section: Introductionmentioning
confidence: 99%